Evaluation of heavy metal pollution in the water resources of van province - Süleyman Alemdar; Sema Ağaoğiu; Mustafa Alişarlı; Semiha Dede (Eurasian Journal of Veterinary Sciences)
In the present study, heavy metal (Fe, Cu, Zn, Mn, Cd, Cr, Ni and Co) levels of the water resources such as well, stream, fountain, tap and tank water obtained from the city of Van and its provinces were investigated For this purpose, from 100 locations, four times from each locations being at spring, summer, autumn and winter, 366 samples were used as material. According to results; Mn and Cd values in all water samples, Fe values taken from well and fountain samples obtained from city center and its provinces and Zn values taken from wells obtained from city center were not in accordance given in the Turkish Drinking Water Standards, Furthermore, Fe. Mn, Cd and Ni concentrations in fountain samples obtained from city center and its provinces, Mn, Cd and Ni in tap water samples, Mn and Cd in tank water samples and Ni levels in tank water samples obtained from towns were not appropriate given in the related regulations.